The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.neuron.2008.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Heterosynaptic Molecular Dynamics: Locally Induced Propagating Synaptic Accumulation of CaM Kinase II

Abstract: Calcium-calmodulin-dependent protein kinase II (CaMKII) is a key mediator of synaptic plasticity and learning. Global pyramidal cell glutamate stimulation induces translocation of CaMKII from dendritic shafts to spines. Here we show that local dendritic stimulation by puffing glutamate onto a region containing 7-32 synapses induces translocation of CaMKII to synapses initially at the puff site, but that translocation subsequently spreads within dendrites to the distal dendrite arbor, resulting in a persistent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
112
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(129 citation statements)
references
References 39 publications
12
112
5
Order By: Relevance
“…Interestingly, it has been shown that an alteration of the inhibitory phosphorylation function of the Ca 2+ /calmodulin‐dependent protein kinase II (CamKII) is coupled to an increase in AMPA receptors expressed at the synapse (Rose, Jin, & Craig, 2009). In addition, mutations affecting this critical site of CamKII were shown to prevent the behavioral deficit in UBE3A gene‐altered mice, suggesting that the Angelman syndrome is associated with a perturbation of CamKII functions (van Woerden et al., 2007; Figure 1).…”
Section: Reviewmentioning
confidence: 99%
“…Interestingly, it has been shown that an alteration of the inhibitory phosphorylation function of the Ca 2+ /calmodulin‐dependent protein kinase II (CamKII) is coupled to an increase in AMPA receptors expressed at the synapse (Rose, Jin, & Craig, 2009). In addition, mutations affecting this critical site of CamKII were shown to prevent the behavioral deficit in UBE3A gene‐altered mice, suggesting that the Angelman syndrome is associated with a perturbation of CamKII functions (van Woerden et al., 2007; Figure 1).…”
Section: Reviewmentioning
confidence: 99%
“…2. This is a reasonable approximation, since the Ca 2+ spike travels much faster than the CaMKII translocation wave (Rose et al 2009). Thus by the time a significant amount of activated CaMKII has diffused into non-stimulated regions of the dendrite, any CaMKII encountered there will already be primed.…”
Section: Model Of Camkii Translocation Wavesmentioning
confidence: 98%
“…Our previous mathematical model of CaMKII translocation waves within a dendrite (Earnshaw and Bressloff 2010) is based upon an experimentally motivated mechanism proposed by Rose et al (2009), which is illustrated in Fig. 2.…”
Section: Model Of Camkii Translocation Wavesmentioning
confidence: 99%
See 2 more Smart Citations